Primary Chinese school English language teachers’ perceptions towards the usage of Google Classroom - Sashveta Darsyini, Segaran (2021)
This study explored on the primary Chinese school English Language teachers’ perceptions on the effectiveness in the usage of Google Classroom and the challenges faced by them in using it. Both qualitative and quantitative methods were used in this research study. There were 30 primary Chinese school English Language teachers from 5 different schools in Ipoh whom participated in this research study. All 30 participants were involved in answering the questionnaire in which 5 of the participants were involved in a semi-structured interview as well. The findings of this research study identified that majority of the primary Chinese school English Language teachers were satisfied with the usage of Google Classroom due to its effectiveness as an active teaching and learning tool. However, this research study also found out that all the primary Chinese school English Language teachers do face challenges in using Google Classroom due to external factors.